Erythropoietin in vasospasm. From bench to bedside? - Welling, Leonardo Christiaan; Welling, Mariana Schumacher; Figueiredo, Eberval Gadelha; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2014)
Aneurysmal subarachnoid haemorrhage is one of the most deleterious acute neurological diseases. The cerebral ischemia secondary to arterial vasospasm occurring after aneurysmal subarachnoid haemorrhage is still responsible for the considerable morbidity and mortality in these patients. Besides the knowledge of basic mechanisms of cerebral vasoespasm following aneurysmal subarachnoid haemorrhage, the prophylaxis and treatment of this pathology however still remain suboptimal. There is some evidence that acute erythropoietin treatment may reduce the severity of cerebral vasospasm and eventually improve outcome in aneurysmal subarachnoid haemorrhage patients. There are underlying mechanisms extend far beyond erythropoiesis: like enhancing neurogenesis, decreasing inflammation and apoptosis inhibition. In this review the authors describe many of the biologic effects, especially experimental studies and clinical studies that reported why the erythropoietin could be beneficial to patients with aneurysmal subarachnoid haemorrhage.
Keywords: Subarachnoid hemorrhage; vasospasm intracranial; erythropoietin